Improvements in Wireless Communication and Support for WMSN in IEEE 1451 - Rufino, Leonardo Maccari; Steiner, Rodrigo Vieira; Raimundo, Rodrigo Valceli; Fröhlich, Antônio Augusto (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2014)
The IEEE 1451 smart transducer interface standard aims at establishing a common interface to promote interoperability among the myriad of transducers currently in the market. Nonetheless, the acceptance of the standard in the realm of Wireless Sensor Networks (WSN) seems to be constrained by apparently incompatible operational semantics: while ordinary transducers deployed in control networks usually operate at fixed periods, or even as slaves of master controllers, wireless sensors mostly avoid such regimens due to its inherent energy and bandwidth utilization inefficiency. In this paper, we propose a reconciling strategy based on Transducer Interface Module Initiated Message (TIM-IM) that enables Wireless Transducer Interface Modules (WTIM) to communicate efficiently with a Network Capable Application Processor (NCAP). We also propose an adjustment to the IEEE 1451 project in order to enable its use in Wireless Multimedia Sensor Networks (WMSN). The proposed solution has been validated through a prototype implementation with expressive efficiency gains.